Utilization of CT Pulmonary Angiography in Suspected Pulmonary Embolism in a Major Urban Emergency Department - Shujaat, Adil; Shapiro, Janet M.; Eden, Edward (Pulmonary Medicine, 2013)
Objectives. We conducted a study to answer 3 questions: (1) is CT pulmonary angiography (CTPA) overutilized in suspected pulmonary embolism (PE)? (2) What alternative diagnoses are provided by CTPA? (3) Can CTPA be used to evaluate right ventricular dilatation (RVD)? Methods. We retrospectively reviewed the clinical information of 231 consecutive emergency department patients who underwent CTPA for suspected PE over a one-year period. Results. The mean age of our patients was 53 years, and 58.4% were women. The prevalence of PE was 20.7%. Among the 136 patients with low clinical probability of PE, a d-dimer test was done in 54.4%, and it was normal in 24.3%; none of these patients had PE. The most common alternative findings on CTPA were emphysema (7.6%), pneumonia (7%), atelectasis (5.5%), bronchiectasis (3.8%), and congestive heart failure (3.3%). The sensitivity and negative predictive value of CTPA for (RVD) was 92% and 80%, respectively. Conclusions. PE could have been excluded without CTPA in ~1 out of 4 patients with low clinical probability of PE, if a formal assessment of probability and d-dimer test had been done. In patients without PE, CTPA did not provide an alternative diagnosis in 65%. In patients with PE, CTPA showed the potential to evaluate RVD.